“Of War Tanks and Military Memorabilia”: A Look at the Conservation of Military Collections at the Zimbabwe Military Museum (ZMM) - Simbarashe Shadreck Chitima; Amos Zevure (SAGE Publications, 2023)
A historiography of museums since the cabinets of curiosity shows evidence that museums have been seized with the acquisition, conservation, and exhibition of collections for public consumption. National museums have, in different contexts, assumed the role of public heritage protector and educator of national history. They have also served as a vehicle for negotiating national identities. As museums seek to good care of its collections, the public’s expectation is that their heritage is in good hands when under museum administration. Sometimes, however, due to several challenges that are context specific this role has been found not to be easy. This study focuses specifically on evaluating the efficacy of conservation measures of artifacts on display employed at the Zimbabwe Military Museum (ZMM). The study employed qualitative and case study research approaches where interviews as well as observations were deployed as research instruments. The study reveals that artifacts in display cases and those in open displays are deteriorating at un-precedented levels chiefly due to lack of purpose built infrastructure, conservation equipment, policy frameworks, and staff training. Identified agents of deterioration were human factors, light, pollution, temperature and relative humidity. In addition, statues were broken, metal collections corroding, paper and photographs fading, and showing signs of discoloration as well as textile collections weakening. In sum, conservation measures employed at the ZMM are constrained hence artifacts on display are more susceptible to deterioration and destruction.